Fighting for the forest : how FDR's Civilian Conservation Corps helped save America - Pearson, P. O'Connell (Patricia O'Connell) (Simon & Schuster Books for Young Readers, 2020)
Provides a history of Franklin D. Roosevelt's initiative to put hundreds of thousands of people back to work during the Great Depression through his creation of the Civilian Conservation Corps, which resulted in the renovation or construction of hundreds of state and national parks across America.